Jujuboside B Inhibits Neointimal Hyperplasia and Prevents Vascular Smooth Muscle Cell Dedifferentiation, Proliferation, and Migration via Activation of AMPK/PPAR-γ Signaling - Ji, Zaixiong; Li, Jiaqi; Wang, Jianbo (Frontiers in Pharmacology, 2021)
The uncontrolled proliferation and migration of vascular smooth muscle cells is a critical step in the pathological process of restenosis caused by vascular intimal hyperplasia. Jujuboside B (JB) is one of the main biologically active ingredients extracted from the seeds of Zizyphus jujuba (SZJ), which has the properties of anti-platelet aggregation and reducing vascular tension. However, its effects on restenosis after vascular intervention caused by VSMCs proliferation and migration remain still unknown. Herein, we present novel data showing that JB treatment could significantly reduce the neointimal hyperplasia of balloon-damaged blood vessels in Sprague-Dawley (SD) rats. In cultured VSMCs, JB pretreatment significantly reduced cell dedifferentiation, proliferation, and migration induced by platelet-derived growth factor-BB (PDGF-BB). JB attenuated autophagy and reactive oxygen species (ROS) production stimulated by PDGF-BB. Besides, JB promoted the phosphorylation of adenosine monophosphate-activated protein kinase (AMPK) and the expression of peroxisome proliferator-activated receptor-γ (PPAR-γ). Notably, inhibition of AMPK and PPAR-γ partially reversed the ability of JB to resist the proliferation and migration of VSMCs. Taken as a whole, our findings reveal for the first time the anti-restenosis properties of JB in vivo and in vitro after the endovascular intervention. JB antagonizes PDGF-BB-induced phenotypic switch, proliferation, and migration of vascular smooth muscle cells partly through AMPK/PPAR-γ pathway. These results indicate that JB might be a promising clinical candidate drug against in-stent restenosis, which provides a reference for further research on the prevention and treatment of vascular-related diseases.